See the cat ebook Three stories about a dog. - LaRochelle, David (See the Cat., 2021)
Winner of the 2021 Theodor Seuss Geisel Award Move over, Spot. . . . Spoofing classic primers, Max the Dog talks back to the book in a twist that will have fans of funny early readers howling. See Max. Max is not a cat—Max is a dog. But much to Max's dismay, the book keeps instructing readers to "see the cat." How can Max get through to the book that he is a DOG ? In a trio of stories for beginning readers, author David LaRochelle introduces the excitable Max, who lets the book know in irresistibly emphatic dialogue that the text is not to his liking. Illustrator Mike Wohnoutka hilariously depicts the pup's reactions to the narrator and to the wacky cast of characters who upend Max's—and readers'—expectations as the three stories build to an immensely satisfying conclusion. Hooray, Max, hooray!